THE INFLUENCE OF GROUP TASK TOWARDS STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT - WIRATNO, PURNA (Lentera: Jurnal Ilmiah Kependidikan, 2019)
Language is a very important thing for human around the world because language is used in all aspects of human life. People use language to communicate with each other and to get knowledge. The objective of this research is to find out the influence of using group task as a technique in teaching writing ability at SMP level. The writer conducted the research at the first semester of the eighth class of SMP Muhammadiyah 1 Way Sulan South Lampung in 2017/2018. There were two classes namely class VIIIA for experimental class and class VIIIB for control class. As the sample consists of 59 students. The sample was taken by using total random sampling technique. After analyzing the data by using t-test formula, it was found that ttest > ttable = 7.11 > 2.00. It  means that there was positive influence of group task towards students’ writing narrative text ability at the first semester of the eighth class at SMP Muhammadiyah 1 Way Sulan South Lampung in 2017/2018.